Efektivitas Metode Phonic Dalam Meningkatkan Kemampuan Membaca Permulaan Bagi Anak Berkesulitan Belajar Membaca - Nera Lestari; Asep Ahmad Sopandi (Jurnal Penelitian Pendidikan Khusus, 2023)
This study aims to prove that the phonic method is effective in improving early reading skills, especially CV-CVC pattern words for children with learning difficulties in grade IV at SDN 17 Jawa Gadut. This research is one type of experimental research with a single subject that uses the A-B-A design. The data analysis technique used is a graphical visual analysis technique. A total of 16 meetings were held. With the results of the data from the A1 baseline activity is 0%, 0%, 0%, 0%. Intervention (B) with data results are 40%, 47%, 67%, 67%, 73%, 80%, 80%, 80%. Then at baseline A2, the results obtained are 80%, 87%, 93% and 93%. Looking at the results of the research that has been described, it proves that the ability of children to read KV-CVC patterned words using the phonic method increases in every condition seen from the value obtained by the child.